Peculiarities of unhappy woman's fate modeling in poems of T. Shevchenko (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article describes the details of modeling the unfortunate women’s fate by Taras Shevchenko in his poems «Katerina», «Housemaid», «Princess». The author’s approach to reflect the tragic-dramatic situations that have a crucial role for the heroines, and social trends that lead to women’s suffering are studied.
Keywords: women images; gender problems; modeling; author’s position; poetics